A “antiga religião” moderna: uma análise fatorial da Wicca de Gerald - Arantes, Flávio Lopes (2023)
The purpose of this dissertation is to analyze the structural elements of Wicca, a religion established by Gerald Gardner in the mid-20th century in England. We seek to develop a factorial model that outlines its fundamental characteristics based on the works published by Gardner and his collaborators. To achieve this, we employ the multidimensional approach proposed by Glock and Stark (1968), which allows us to describe Gardnerian Wicca in the following dimensions: institutional organization, body of practices, subjective experience, transmission of knowledge, and set of beliefs. Regarding the analysis of the latter, we apply the comparative model of religious beliefs proposed by Usarski (2020). This model, by offering a systematic description oriented around two contrasting poles, encompasses the following categories of a religious doctrine: ontology, theology, access to the divine, chronology, anthropology, and soteriology. The findings reveal that Gardnerian Wicca, although considered a religion developed from the Western esoteric milieu, incorporates various principles deemed typically Eastern in its structure. The emergence of this new religion is the result of multiple influences that, combined, have established a unique and differentiated spiritual tradition